Case report of cerebral cystic echinococcosis in a 5-year-old child - Menschaert, Denis; Daron, Aurore; Frere, Julie (Frontiers in Tropical Diseases, 2023)
Cystic echinococcosis is a zoonosis caused by the larval form of the tapeworm Echinococcus granulosus. It has a worldwide distribution and represents a particularly significant economic and health burden in endemic areas. The most affected organs are the liver and the lungs. Cerebral involvement is relatively rare. This is a case study of a clinical presentation of cerebral cystic echinococcosis in a 5-year-old female patient of Moroccan origin who had developed recurrent seizures. Currently, diagnosis is based on radiological imaging in the context of anamnestic suspicion. Beyond the conclusions that can be drawn from the various case reports, there are no guidelines on management methods or randomized controlled trials that have compared management methods, and their absence can be deleterious for children. We present this clinical case report to add to the existing ones and to assist clinicians in their therapeutic decision-making while they await guidelines.